Beginning programming all-in-one for dummies - Wang, Wally (For Dummies, 2022)
Let there be code! Beginning Programming All-in-One For Dummies offers one guide packed with 7 books to teach you programming across multiple languages. Coding can seem complex and convoluted, but Dummies makes it simple and easy to understand. You'll learn all about the principles of programming, algorithms, data structures, debugging programs, unique applications of programming and more while learning about some of the most popular programming languages used today. Move confidently forward in your computer science coursework or straight into the workforce. You'll come away with a rock-solid foundation in the programming basics, using data, coding for the web, and building killer apps. Learn the basics of coding, including writing and compiling code, using algorithms, and data structures Get comfortable with the syntax of several different programming languages Wrap your mind around interesting programming opportunities such as conducting biological experiments within a computer or programming a video game engine Develop cross-platform applications for desktop and mobile devices This essential guide takes the complexity and convolution out of programming for beginners and arms you with the knowledge you need to follow where the code takes you.